A Longitudinal Analysis of Burnout in Middle and High School Korean Teachers. (20th December 2012) - Park, Yang Min; Lee, Sang Min
Abstract This study examines longitudinal relationships among three burnout dimensions in middle and high school teachers. For this study, 419 middle and high school teachers participated in a panel survey, which was conducted in three waves. Using Amos 7.0, we performed autoregressive cross‐lagged modeling to obtain a complete picture of the longitudinal relationships among the three factors of the Maslach Burnout Inventory‐Educator Survey. Results indicated that the paths from emotional exhaustion at Time1 and Time2 to depersonalization at Time2 and Time3 were statistically significant. In addition, the paths from personal accomplishment at Time1 and Time2 to depersonalization at Time2 and Time3 were also statistically significant. Empirically identifying the process by which burnout occurs could help practitioners and policy makers to design burnout prevention strategies. Copyright © 2012 John Wiley & Sons, Ltd.